First record of margay (Leopardus wiedii) in the Sierra Monte Negro State Reserve, Morelos, México: the importance of low deciduous forest relicts for conserving the species - Vera-García, Zuri Samuel; Fuentes-Vargas, Liliana; Weston-Flores, Mariam; Uriostegui-Velarde, Juan Manuel (Therya Notes, 2023)
The margay (Leopardus wiedii), locally known as tigrillo, is a small wild felid distributed from México to South America, mainly in tropical and temperate environments. In Morelos, its presence was previously recorded in 2 federal protected natural areas: the Chichinautzin Biological Corridor Flora and Fauna Protection Area, Fraction I (APFF-CBC) to the north and the Sierra de Huautla Biosphere Reserve (REBIOSH) to the south. To obtain information on the presence of wild mammals in the Sierra Monte Negro State Reserve (RESMN), monitoring was carried out using camera traps. RESMN is an important State Protected Natural Area for its potential role as a biological corridor between APFF-CBC and REBIOSH. However, few studies have been conducted on the species of wild mammals distributed in RESMN. The monitoring was performed between November 2020 and November 2021, placing 10 camera-trap monitoring stations with a total sampling effort of 3,650 trap-days. A single margay individual was recorded in 2 monitoring stations between November 2020 and April 2021, indicating that this individual used the RESMN at least during the dry season. The presence of this margay individual demonstrates the importance of RESMN, which may serve as a habitat or corridor for felids of this species.